Habitat use by burnished-buff tanager (Tangara cayana) and great antshrike (Taraba major) in a human-modified landscape in southeast Brazil - de Meira, Natália Tony [UNESP]; Rodrigues, Ramon Juliano [UNESP]; Toledo, Maria Cecília; Frei, Fernando [UNESP] (My University, 2018)
· The agricultural expansion in tropical regions is causing loss and reductions habitat, as well as changes in biodiversity. Intrinsic ecological factors, such as trophic level, and habitat conditions, such as vegetation structure, can determine how a particular species uses the habitat. The Brazilian savanna is a world biodiversity hotspot and the most threatened in the country, with a higher deforestation rate than the Amazon. Therefore, it is important to understand how the presence/absence of forest-dependent birds is affected by local characteristics and by landscape features of habitat remnants. Here we study patterns of habitat use in two forest-dependent bird species, Burnished-buff Tanager (Tangara cayana) and Great Antshrike (Taraba major), to learn how characteristics at the local and landscape scales can influence their occurrence in forest remnants. This work was carried out in a forest remnant area embedded in a human transformed landscape, belonging to the Cerrado biome, Brazilian Savanna. The study area is localized in the municipality of Assis, São Paulo State. The selected area was delimited and divided into 120 quadrants of 22,500 m 2 each. In the center of each quadrant we positioned one observation point. The points were visited three times and presence/absence data for both species were collected using playback. For each point we recorded local characteristics – interior vs edge, canopy height, canopy cover, presence of dead standing trees, dead trees with arthropods, trees with fruits, and grasses; and landscape characteristics – distance to water bodies, distance to floodplain (várzea), distance to nearest farmland, highways, unpaved roads, railroads, and houses. Our results indicate that T. cayana was more likely to be present in points located at the forest edge, close to water bodies and with high canopy. In addition, the distance from farming activity was the variable with most influence on the occurrence of T. major. The final models for each species predicted patterns of presence/absence correctly in 73% of cases for T. cayana and 76% for T. major. The results have implications for the conservation of forest specialist species that occupy forest remnants in deeply modified landscapes and can contribute to designing proper management plans.
Keywords: Anthropic factors; Fragmentation; Presence-absence models; Riparian forests; Tamnophilidae; Thraupidae